Cardiac diagnostic work-up for atrial fibrillation after transient ischaemic attacks in England and Wales: results from a cross-sectional survey. Issue 11 (10th November 2016) - Geraghty, Olivia; Korompoki, Eleni; Filippidis, Filippos T; Rudd, Anthony; Veltkamp, Roland
Abstract : Objectives: Transient ischaemic attacks (TIAs) are an important precursor of stroke. Atrial fibrillation (AF) is among the most dangerous aetiologies shared between TIAs and strokes. Detection of AF after TIAs is essential for the initiation of oral anticoagulants. We aimed to identify variations in the use of cardiac investigations used to detect AF and cardiac pathology in patients with TIA in the UK. Setting: All TIA clinical leads in England and Wales received an invitation by email to participate in an online survey in February 2015. The questionnaire consisted of 36 multiple choice questions covering the domains: (1) general information about stroke units, (2) ECG diagnostics and cardiologic work-up and (3) management of AF. Results: 146 survey invitations were sent. The response rate was 40% (n=59). Diagnosis of AF largely depends on medical history and 12-channel ECG which is performed in the vast majority of patients with TIA (>75%) in 94.1% of the TIA services. Many patients with TIA either do not receive 24-hour Holter recording (requested regularly in 42% of the services) or only after considerable delay (>2 weeks). Prolonged event recording is only rarely performed (16%). Only about half of patients with TIA undergo echocardiography. Cranial imaging in patients with TIA is mainly performed as CT (62%). The majority of TIA clinics rapidly initiate anticoagulation in TIA patients with AF (81.6%) preferably using new oral anticoagulants (75.5%). Conclusions: Significant variation in the cardiac diagnostic work-up following TIA exists regarding the use of particular detection techniques and the duration of cardiac ECG monitoring. Only limited resources are allocated to cardiac evaluation. In addition to research establishing the optimal ECG technique for patients with TIA, healthcare delivery programmes are needed to ensure proper management to prevent strokes.